Nonisothermal crystallization behaviors of nanocomposites of poly(vinylidene fluoride) and multiwalled carbon nanotubes. (7th April 2015) - Lim, Jun Young; Kim, Jihun; Kim, Sehyun; Kwak, Soonjong; Lee, Youngchul; Seo, Yongsok
Abstract: A kinetic equation for the nonisothermal crystallization was employed to analyze the crystallization behaviors of poly(vinylidene fluoride)/multiwalled carbon nanotube (PVDF/MWCNT) composites and its polymorph development. The Avramic exponent, n, could be reasonably well determined from the nonisothermal crystallization exotherm. The polarized optical microscopy showed that both neat PVDF and the nanocomposites had well-developed spherulite morphology. Most crystallization phase of the composite had only α-phase. Without an external stimulus, development of β-phase responsible for the piezoelectric properties of PVDF was not observed. Nonisothermal analysis implicitly provides the clue of morphological development history as well as PVDF molecular ordering around the foreign nuclei. Graphical abstract: Highlights: A kinetic equation for the nonisothermal crystallization was employed to analyze the crystallization behaviors. Most crystallization phase of the composite had only α-phase. Without an external stimulus, development of β-phase of PVDF was not observed. Nonisothermal analysis provides the clue of morphological development history and PVDF molecular ordering.